Analisis Konsep Matematika dalam Permainan Tradisional Engklek Sebagai Kajian Etnomatematika pada Siswa Sekolah Dasar - Rohmah, Tri Iftitahur; Putri, Vera Zunita; Tabina, Melia Hansa Cordelia; Zuliana, Eka (Papanda, 2026)
This study aims to identify and analyze the mathematical concepts contained in the traditional game of engklek as an ethnomathematics study. This study uses a qualitative approach with ethnographic methods conducted in Rahtawu Village, Gebog District, Kudus Regency. Data sources were obtained through interviews with Rahtawu Village elders and documentation of engklek game patterns and activities that are still preserved by the local community. The results show that the engklek game contains concepts of plane geometry through square, rectangular, and semicircular grid patterns, as well as grid arrangements that resemble a cuboid net. In addition, the movements of players in jumping, maintaining balance, and following the grid lines demonstrate the application of the concepts of angles, directions, trajectories, and spatial coordination. These findings indicate that the engklek game has the potential as a source of ethnomathematics studies that can be used to link mathematical concepts with local culture in the context of elementary school learning.